The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.14744/tjtes.2020.73537
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of demographic, clinical, and histopathological features of patients who underwent appendectomy due to a presumed diagnosis of acute appendicitis

Abstract: BACKGROUND:To compare the clinical, biochemical, and histopathological features of patients who underwent appendectomy due to a presumed diagnosis of acute appendicitis (AAp). METHODS:The demographic, biochemical and histopathological data of 8206 patients who underwent appendectomy for AAp between January 2006 and March 2014 were retrospectively analyzed in this study. Patients were compared regarding the following characteristics: disruption by season (autumn vs. winter vs. spring vs. summer), working days (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…The greater use of CT imaging during the pandemic is likely to explain the lower negative appendicectomy rate seen during the pandemic. Outside of the pandemic, a negative appendicectomy rate of 9.7% was reported in a retrospective study of 8206 patients [ 28 ], which is consistent with what is widely reported in the literature. In our cohort, the negative appendicectomy rate nearly halved during the pandemic to 5.7%, whilst the rate of CT prior to operation increased by approximately 10%.…”
Section: Discussionsupporting
confidence: 85%
“…The greater use of CT imaging during the pandemic is likely to explain the lower negative appendicectomy rate seen during the pandemic. Outside of the pandemic, a negative appendicectomy rate of 9.7% was reported in a retrospective study of 8206 patients [ 28 ], which is consistent with what is widely reported in the literature. In our cohort, the negative appendicectomy rate nearly halved during the pandemic to 5.7%, whilst the rate of CT prior to operation increased by approximately 10%.…”
Section: Discussionsupporting
confidence: 85%
“…Akbulut et al, suggested that a relationship exists between demographic features, histopathological findings of appendectomy specimens, seasons, days of the week, and working days in patients undergoing appendectomy [ 14 ]. Meanwhile the current study, focused on the surgical approach, fund that patients in the laparoscopic group had significantly higher operative time (74.32 ± 1.12) compared to patients in the open surgery group (47.86 ± 3.31) (p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…AA occurs year-round, but certain months have higher rates. Some authors have linked AA, demographics, and seasons 7 .…”
Section: Introductionmentioning
confidence: 99%